2011
DOI: 10.1007/s00262-011-1095-2
|View full text |Cite
|
Sign up to set email alerts
|

Human kallikrein 4 signal peptide induces cytotoxic T cell responses in healthy donors and prostate cancer patients

Abstract: Immunotherapy is a promising new treatment for patients with advanced prostate and ovarian cancer but its application is limited by the lack of suitable target antigens that are recognized by CD8 + cytotoxic T lymphocytes (CTL). Human kallikrein 4 (KLK4) is a member of the kallikrein family of serine proteases that is significantly over-expressed in malignant versus healthy prostate and ovarian tissue, making it an attractive target for immunotherapy. We identified a naturally processed, HLA-A*0201-restricted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…We can ascribe this strong and broad immune response to the lipophilic sequences within SP domains, such as MUC1‐SP‐L, which has been shown by us (Kovjazin et al , ,b, ; Kovjazin & Carmon, ) and others (Wilkinson et al , ; Kerzerho et al , ) to be more immunogenic than other protein domains, and which, in the case of ImMucin, can generate a rapid response, using a low dose of naked LP administered in conjunction with hGM‐CSF, without employing a dedicated ‘carrier system’ or specific adjuvants. In contrast, other anti‐MUC1 vaccination strategies primarily induce humoral responses and/or selected CD8+ T‐cell activation in a subset of patients (Roulois et al , ).…”
Section: Discussionmentioning
confidence: 80%
“…We can ascribe this strong and broad immune response to the lipophilic sequences within SP domains, such as MUC1‐SP‐L, which has been shown by us (Kovjazin et al , ,b, ; Kovjazin & Carmon, ) and others (Wilkinson et al , ; Kerzerho et al , ) to be more immunogenic than other protein domains, and which, in the case of ImMucin, can generate a rapid response, using a low dose of naked LP administered in conjunction with hGM‐CSF, without employing a dedicated ‘carrier system’ or specific adjuvants. In contrast, other anti‐MUC1 vaccination strategies primarily induce humoral responses and/or selected CD8+ T‐cell activation in a subset of patients (Roulois et al , ).…”
Section: Discussionmentioning
confidence: 80%
“…10,11 More recently, it has become evident, that apart from the consensus motif essential for the role of the SP as a targeting signal, SP domains exhibit high antigenic variability and specificity to the proteins they derived from, 8,[12][13][14] enabling them to serve as VCs. Yet, while select MHC class I, [15][16][17] class II 6,18-20 and HLA-E 21,22 single epitopes have already been identified in different SP domains, and shown to specifically activate T-cells, and more rarely inhibit select NK-cells, the broader potential of using the entire SP domains as multi-epitope long peptides (LP) and their ability to induce robust antigenspecific T and B-cell response has not been explored.…”
Section: Antigen Processing and Presentation For T And B-cell Epitopesmentioning
confidence: 99%
“…It is unknown what the potential functional effects of an amino acid substitution are within the signal peptide. However, a recent study has shown that this cleaved peptide may be a useful target in prostate cancer immunotherapy, with the KLK4 signal peptide successfully inducing and expanding the cytotoxic T lymphocyte response more readily than PSA or Prostatic Acid Phosphotase (PAP) [42]. In addition, in silico analysis using the signal peptide prediction program SignalP [43] predicted a Serine22Alanine substitution to alter the cleavage site from aa 26/27 to aa 21/22.…”
Section: Discussionmentioning
confidence: 99%